2017
DOI: 10.1093/scan/nsx101
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin promotes altruistic punishment

Abstract: The role of neuromodulators in the enforcement of cooperation is still not well understood. Here, we provide evidence that intranasal applied oxytocin, an important hormone for modulating social behavior, enhances the inclination to sanction free-riders in a social dilemma situation. Contrary to the notion of oxytocin being a pro-social hormone, we found that participants treated with oxytocin exhibited an amplification of self-reported negative social emotions such as anger towards free-riders, ultimately res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…However, altruistic punishment is strongly associated with altered amygdala function (Scheele et al, 2012) and there was no evidence for differential amygdala responses in the PLC and OXT groups. While a previous study has reported that OXT can promote altruistic punishment of defectors, and feelings of anger and disappointment towards them, in an economic game context, it also increases co-operation with them thereby increasing self-gain (Prisoner’s dilemma game: Aydogan et al, 2017). Thus, on balance, it is likely that in the current context OXT primarily biases individuals towards an optimal self-gain strategy, although without simultaneously doing so by overtly damaging others emotionally.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, altruistic punishment is strongly associated with altered amygdala function (Scheele et al, 2012) and there was no evidence for differential amygdala responses in the PLC and OXT groups. While a previous study has reported that OXT can promote altruistic punishment of defectors, and feelings of anger and disappointment towards them, in an economic game context, it also increases co-operation with them thereby increasing self-gain (Prisoner’s dilemma game: Aydogan et al, 2017). Thus, on balance, it is likely that in the current context OXT primarily biases individuals towards an optimal self-gain strategy, although without simultaneously doing so by overtly damaging others emotionally.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have reported that OXT can promote lying for the benefit of in-group members, including participants themselves, although not lying purely for self-gain (Shalvi, & De Dreu, 2014) and that it reduced honesty for personal gain only in a competitive environment (Aydogan et al, 2017). However, OXT can also in some circumstances promote pure self-serving lying to increase personal gain in men when there is no risk of discovery (Sindermann et al, 2018) and can increase acceptance of self-benefit moral dilemmas, but importantly not acceptance of other types of moral dilemma (Scheele et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This is also not likely to be a ceiling effect, as there is no oxytocin effect on increasing prosociality even when prosocials employ a more "self-centered" reference-point in a competitive context. Oxytocin has been implicated in many social behaviors, from promoting trust, generosity and cooperation 21,22,46,47 to aggravating mistrust and aggressive behavior 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…However, altruistic punishment is strongly associated with altered amygdala function (Scheele et al, 2012), and there was no evidence for differential amygdala responses in the PLC and OXT groups. While OXT can promote altruistic punishment of defectors, and feelings of anger and disappointment towards them in the Prisoner’s dilemma game, it also increases cooperation with them thereby increasing self-gain (Aydogan et al, 2017a). Thus, in the current context OXT may primarily bias individuals towards an optimal self-gain strategy, although without simultaneously doing so by overtly damaging others emotionally.…”
Section: Discussionmentioning
confidence: 99%
“…Although OXT has often been reported to facilitate prosocial behaviors, it can also promote anti-social ones such as self-serving lying and group-serving dishonesty (Shalvi and De Dreu, 2014; Kendrick et al, 2017; Sindermann, 2018). On the other hand, OXT can also increase altruistic behaviors (Hu et al, 2016; Aydogan et al, 2017a). Thus, although OXT can influence empathy, altruistic, and self-serving behaviors, it is unclear what its functional role may be when these motivations are competing.…”
Section: Introductionmentioning
confidence: 99%